Zakat Scholarly Publication Development in Malaysia and Indonesia: A Bibliometric Analysis - Mansyur, Abdurrahman; Rusanti, Ega (Center of Strategic Studies (PUSKAS) BAZNAS, 2023)
This research aims to analyze the development of zakat research in Malaysia and Indonesia from the Scopus database. Keywords “Zakat” or “Zakah” or “Islamic Social Finance” were used to harvest the data, yielding 364 articles from Malaysia and 295 documents from Indonesia. Machine learning tools, i.e., Bibliometrix via R-Studio and VOSViewer were employed for the bibliometric study. The Scopus database has recorded zakat publications from Malaysia since 1997, and from Indonesia since 2008. Saad R A J and Widiastuti T marked the most Malaysian and Indonesian influential authors with 18 and 14 documents, respectively. Further comparative analysis was done, showcasing the differences between the two countries in terms of international collaboration, trending topics and other scholarly measures related to the zakat administration discussed in the publications of Malaysian and Indonesian scholars.